Institutional Branding and Media Visibility in Higher Education: A Theoretical Model for Strategic Communication Management - Al Yahyaei, Nasser; Al Senani, Iman (Journal of Cultural Analysis and Social Change, 2025)
This conceptual study aims to explain how higher education institutions (HEIs) can strengthen institutional branding through strategic communication. It develops a theoretical model linking strategic communication capability (SCC) to institutional brand equity via the mediating mechanisms of media engagement, institutional visibility, and perceived legitimacy. The paper employs a conceptual research design grounded in an integrative literature review of Scopus-indexed studies published between 2010 and 2025. Drawing on Institutional Theory, Strategic Communication Theory, and Branding Theory, it synthesizes key insights through thematic integration and theoretical reasoning to construct a comprehensive conceptual framework supported by five propositions. The findings position strategic communication as a dynamic managerial capability that transforms internal competencies into external legitimacy and reputation, with media engagement and visibility identified as key mechanisms driving brand equity. The study provides practical guidance for higher education leaders and policymakers on professionalizing communication functions, enhancing transparency, and leveraging media strategies to strengthen institutional reputation. The research is limited by its conceptual nature and absence of empirical testing; future studies are encouraged to validate the model across different cultural and institutional contexts using mixed methods and longitudinal designs. The study’s social implications lie in its potential to enhance public trust, accountability, and transparency in higher education by fostering open, evidence-based communication practices. Overall, the paper contributes to higher education management literature by integrating communication, legitimacy, and branding theories into a unified model that advances understanding of institutional reputation-building in the digital era.